NHS commissioning in probation in England – Still on a wing and a prayer. (17th June 2019) - Sirdifield, Coral; Marples, Rebecca; Brooker, Charlie; Denney, David
Abstract: Policy reforms in England and Wales mean that all individuals released from prison will have some contact with probation services, either serving a community sentence, or being on licence post‐release. Despite often having complex health needs, including a higher prevalence of mental health problems, substance misuse problems and physical health problems than the general population, this socially excluded group of people often do not access healthcare until crisis point. This is partly due to service‐level barriers such as a lack of appropriate and accessible healthcare provision. We conducted a national survey of all Clinical Commissioning Groups (CCGs, n = 210) and Mental Health Trusts (MHTs, n = 56) in England to systematically map healthcare provision for this group. We compared findings with similar surveys conducted in 2013 and 2014. We had excellent response rates, with the data analysed here representing responses from 75% of CCGs and 52% of MHTs in England. We found that just 4.5% ( n = 7) of CCG responses described commissioning a service specifically for probation service clients, and 7.6% ( n = 12) described probation‐specific elements within their mainstream service provision. Responses from 19.7% of CCGs providing data ( n = 31) incorrectly suggested that NHS England are responsible for commissioning healthcare for probation clients rather than CCGs. Responses from 69% ( n = 20) of MHTs described providing services specifically for probation service clients, and 17.2% ( n = 5) described probation‐specific elements within their mainstream service provision. This points to a need for an overarching health and justice strategy that emphasises organisational responsibilities in relation to commissioning healthcare for people in contact with probation services to ensure that there is appropriate healthcare provision for this group.